THE COUNTLESS POSSIBILITIES OF THE CHILD’S BRAIN ON THE AUTISM SPECTRUM: FOCUS, INTELLIGENCE, AND PATHWAYS TO HIGH PERFORMANCE - Cristiane Fragoso Santos, Quelen (Health and Society, 2026)
This article revisits the literature on the cognitive profile of children with Autism Spectrum Disorder (ASD), with special attention to focus abilities, processing speed, rule-based learning, and high performance in specific tasks. It examines how neuropsychological differences – sometimes called “hyperfocus,” high levels of systematization, or exceptional talents – can contribute to high-performance profiles, as well as the underlying brain mechanisms and environmental/interventional factors that favor the flourishing of these potentialities. The discussion also addresses implications for educational and therapeutic interventions, emphasizing an integrative approach that values ​​strengths and neuroplasticity in the context of ASD.